Energy-Efficient Physical Layer Security for Wearable IoT Devices - Zandamela, Abel Abdul; Marchetti, Nicola; Narbudowicz, Adam (My University, 2023)
This work proposes an energy-efficient Directional Modulation (DM) scheme for on-body Internet of Things (IoT) devices. DM performance is tested using a 5-port stacked-patch MIMO antenna under two scenarios: free space case and using a four-layer human forearm phantom to simulate the user’s wrist. It is demonstrated that the scheme achieves steerable secure transmissions across the entire horizontal plane. With low Bit Error Rate (BER) of 1.5 × 10−5 at the desired directions, eavesdroppers experience a high error rate of up to 0.498. Furthermore, this work investigates the DM performance using a subset of the stacked patches in the MIMO antenna, revealing that some combinations achieve a low BER performance using a lower antenna profile, albeit high side-lobes of BER< 10−2 seen outside the desired region. Overall, the solution is proposed as a good candidate to enable secure wireless communications in emerging wearable IoT devices that are subject to size and energy-constraints.
Proceedings of the 17th European Conference on Antennas and Propagation
PUBLISHED
Florence, Italy
Keywords: MIMO Antennas; Directional Modulation; Physical Layer Security; Multimode Antennas; Internet of Things; Telecommunications; Networks and telecommunications research